The Impact of Salary Increase Projection Assumptions on the Difference in Pension Liability Value between the Projected Unit Credit and Traditional Unit Credit Methods - Sena Miftahul Aziz; Oksigeno Phanca Perdana (Research Collaboration Community (RCC), 2025)
The calculation of pension liabilities in defined benefit plans is highly influenced by the actuarial method and economic assumptions applied, particularly salary growth projections. This study aims to analyze the impact of salary increase assumptions on pension liabilities using two commonly adopted actuarial methods: Projected Unit Credit (PUC) and Traditional Unit Credit (TUC). Simulations were conducted using dummy data across three salary groups with varying annual salary growth assumptions, allowing for a comparative analysis of the resulting liabilities from both methods. The results show that PUC consistently produces significantly higher pension liabilities than TUC, with the difference increasing as the assumed salary growth rate rises. This demonstrates the higher sensitivity of the PUC method to future salary projections, which may lead to a more realistic but financially heavier burden on the company. This study offers valuable insights for decision makers in selecting appropriate actuarial methods for pension liability valuation based on their financial strategies and risk tolerance.